Carbon Metabolic Profiling as a Response to Previous Plant Mycotrophy and Soil Disturbance in Wheat Growth - Taiana Conceição; Galdino Andrade; Isabel Brito (Applied Microbiology)
Soil microorganisms play a significant role in the dynamic regulation of organic matter in soils. To assess the influence of agricultural practices on soil functional profiling, we examined the effect of soil disturbance and plant sequence with different levels of mycotrophy on wheat microbiomes metabolism. Soil samples were analyzed with community-level physiological profiles (CLPP) using Biolog™ Ecoplates. The results of average well color development (AWCD) showed that the degree of mycotrophy of preceding crop and soil disturbance affected the soil microbiome, although no impact on Shannon Evenness Index was observed during the experiment. The Shannon–Wiener Diversity Index showed variations among the different preceding plants, but not in wheat analysis. The pattern of the C sources metabolism also changed differentially regarding plant type and soil disturbance during the experiment, being also different within the highly mycotrophic plants (legume and grass). In the legume, an increase in the metabolism of amine/amides and phenolic acids was observed, whilst in the grass, an increase in the metabolism of phosphate-carbons (P carbon) and carbohydrates was more evident. Principal component analysis showed that a grouping in the distinct phases of the experiment correlated with the widening of the metabolism of amino acids, carboxylic acids, and carbohydrates. The results indicate that soil functional community structure reflects soil agricultural practice conditions. Previous plant types and soil disturbance impacted the soil microbiome metabolic response (AWCD) in wheat, generating different patterns of carbon metabolism related to previous plant mycotrophy.